Global Dynamics through MSME Purchases Influenced by Price, Quality, and Digital Factors: Dinamika Global melalui Pembelian UMKM Dipengaruhi oleh Faktor Harga, Kualitas, dan Digital - Ferra Puspa Prasiwi; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of digital marketing, service quality, and price on purchasing decisions at MSMEs Rabit Buket Sidoarjo, East Java. Using a quantitative approach, data were collected from 96 respondents through questionnaires and analyzed with SPSS software. Results show that digital marketing, service quality, and price positively and significantly influence purchasing decisions. These findings suggest that MSMEs should enhance their digital marketing, maintain high service quality, and offer competitive pricing to boost customer purchases. Future research should consider additional variables for a more comprehensive analysis. Highlight: Digital marketing enhances purchasing. High service quality influences buyers. Competitive pricing drives purchase decisions. Keyword: Digital marketing, service quality, price, purchasing decisions, MSMEs